Introduction to Law - Akkermans, Bram.; Hage, Jaap.; Waltermann, Antonia (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is exceptional in the sense that it provides an introduction to law in general rather than the law of one specific jurisdiction, and it presents a unique way of looking at legal education. It is crucial for lawyers to be aware of the different ways in which societal problems can be solved and to be able to discuss the advantages and disadvantages of different legal solutions. In this respect, being a lawyer involves being able to reason like a lawyer, even more than having detailed knowledge of particular sets of rules. Introduction to Law reflects this view by focusing on the functions of rules and on ways of arguing the relative qualities of alternative legal solutions. Where 'positive' law is discussed, the emphasis is on the legal questions that must be addressed by a field of law, and on the different solutions which have been adopted by, for instance, the common law and civil law tradition. The law of specific jurisdictions is discussed to illustrate possible answers to questions such as when the existence of a valid contract is assumed.
1 Sources of Law by Jaap Hage -- 2 Legal Reasoning by Jaap Hage -- 3 Basic Concepts of Law by Jaap Hage -- 4 The Law of Contract by Jan Smits -- 5 Property Law by Bram Akkermans -- 6 Tort Law by Jaap Hage -- 7 Criminal Law by Johannes Keiler, Michele Panzavolta, and David Roef -- 8 Constitutional Law by Aalt Willem Heringa -- 9 Administrative Law by Chris Backes and Mariolina Eliantonio -- 10 The Law of Europe by Jaap Hage -- 11 Tax Law by Marcel Schaper -- 12 International Law by Menno T. Kamminga -- 13 Human Rights by Gustavo Arosemena -- 14 Elements of Procedural Law by Fokke Fernhout and Remco van Rhee -- 15 Philosophy of Law by Jaap Hage.
Description based on publisher-supplied MARC data.
Keywords: Law; Law -- Philosophy; Political science; Fundamentals of Law; Philosophy of Law